Optimization of tobacco excise revenue sharing funds utilization by employing structural equation model - Partial least square approach - Amodha, Javas Hasthoka (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to optimize the utilization of Tobacco Excise Revenue Sharing Fund (DBH CHT) in Indonesia by employing the Structural Equation Model (SEM) - Partial Least Square (PLS) approach. The research focuses on enhancing the regulatory framework under Regulation of The Ministry of Finance Number 72/2024 by exploring three key hypotheses: (1) utilization of Tobacco Excise Revenue Sharing Fund (DBH CHT) in alignment with National Strategic Projects (PSN), (2) collaboration with private sectors through Corporate Social Responsibility (CSR) and Public Private Partnership (PPP) schemes, and (3) intervention by the Ministry of Finance in local government fund utilization. Data were collected through an online survey of 145 respondents, predominantly from the Ministry of Finance and regional governments, and analyzed using SmartPLS 4.0. The results indicate that collaboration with CSR/PPP schemes has the most significant positive impact on fund optimization (path coefficient: 0.295, p < 0.05), followed by alignment with PSN (0.255, p < 0.05) and Ministry of Finance intervention (0.199, p < 0.05). Importance-Performance Map Analysis (IPMA) further highlights CSR/PPP collaboration as the highest-priority option due to its very high performance and importance. The study concludes that revising the current regulatory framework to incorporate CSR/PPP collaborations and PSN-aligned utilization can significantly enhance the optimalization of Tobacco Excise Revenue Sharing Fund (DBH CHT). These findings provide actionable policy recommendations for improving regional development and public welfare, though limitations such as sample representativeness and the need for long-term impact assessments are noted.